Spare room at Mary Felix's house - Coates, Carol Lynn (1988)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « A Field Report: Black Duck Brook, Newfoundland March 12-16, 1988 » -- Photo is one of a series associated with a Memorial University folklore student term paper: "A Field Report: Black Duck Brook, Newfoundland March 12-16, 1988"